The Role of Internal Control in Achieving Good University Governance: Empirical Evidence from the University of Jember - Hudi Indra Bayu; Taufik Kurrohman; Ririn Irmadariyani (Harmony Management: International Journal of Management Science and Business, 2026)
This study aims to examine the effect of internal control on Good University Governance at the University of Jember, a state university implementing a Public Service Agency (BLU) financial management pattern. The research employs a quantitative approach with an explanatory design, utilizing primary data collected through questionnaires distributed to 226 respondents selected via purposive sampling. The internal control variable measured based on the five COSO framework components: control environment, risk assessment, control activities, information and communication, and monitoring activities. Meanwhile, Good University Governance is measured through the principles of transparency, accountability, responsibility, independence, and fairness. The findings reveal that internal control has a positive and significant effect on Good University Governance at the University of Jember, with a regression coefficient of 0.940 and a t-value of 25.098. The coefficient of determination (R²) of 0.738 indicates that internal control explains 73.8% of the variation in Good University Governance. These results strengthen the Stewardship Theory perspective, demonstrating that internal control functions not merely as a supervisory mechanism but as a governance mechanism that supports responsible organizational management, risk mitigation, decision-making quality, transparency, and accountability. This research contributes theoretically by expanding the application Stewardship Theory in the context of higher education governance and provides practical implications for university leaders in formulating strategies strengthen internal control systems as an integral part of efforts to improve transparent, accountable, adaptive, and sustainable university governance. The study recommends further research involving multiple universities and incorporating additional variables such as risk management, leadership, organizational culture, and digital transformation.